Sustainable sharia company ecosystem: Independent commissioner and audit committee on Islamic social reporting - Tri Wahyudi; Nur Sabrina; Camka Ayu Pratiwi; Erlina Sari Pohan (Review of Islamic Social Finance and Entrepreneurship, 2023)
Purpose – Disclosure of information is crucial for company values and minimizing conflicts resulting from knowledge asymmetry, especially in social aspects. Stakeholders require information reporting that is transparent, accountable, responsible, and exhaustive. In this study, the independent variables are independent commissioners and audit committees, and the dependent variable is Islamic social reporting. The size of the company served as the control variable for this study.Methodology – The population in this study used sharia companies registered in the Jakarta Islamic Index (JII) for the period 2016-2022. This study used the purposive sampling method and selected 13 companies from a total of 30 companies with data collection twice a year. The analysis technique used is multiple linear regression with SPSSv22 software.Findings – The results of this study show that independent commissioners and audit committees do not affect Islamic social reporting.Implications – This study aims to determine the influence of independent commissioners and audit committees on Islamic social reporting.Originality – This study has originality in the form of Islamic Social Reporting (ISR) proxy variables, which combines the ISR disclosure index designed by Haniffa and Cooke (2002) and Othman and Thani (2010). There are 48 ISR disclosure items divided into six themes. In addition, in this study, there is a control variable, namely the size of the company used to improve the accuracy of the research